Fenomena Lucio pada pasien Morbus Hansen tipe Lepromatosa: Suatu Laporan Kasus Langka - Amalia, Irma; Widayati, Agnes Sri; Ametati, Holy; Rahmat Sugianto, Yosep Ferdinand; Windayati, Sri (RSUP Dr. Kariadi, 2023)
BACKGROUND: Lucio’s phenomenon is a rare leprosy reaction, characterized by severe necrotic cutaneous lesions that generally occur in patients with untreated or inadequately treated lepromatous leprosy (LL). OBJECTIVE: to describe and comprehend the diagnosis and management of Lucio’s phenomenon in leprosy patients CASE: Male, 34 years old with extensive wounds on both arms and legs. About 3 years earlier, the patient felt burning heat in both hands and feet followed by loss of eyebrows and eyelashes, and a change in the shape of the nose. The patient had not received previous therapy. Physical examination showed that the patient appeared anaemic, leonine facies, megalobuli, madarosis, saddle nose, thickening of the ulnar and posterior tibial nerves, deformities of the fingers and toes, and amputations of several fingers. The dermatological status showed multiple ulcers of irregular shape and varying sizes with pus and necrotic tissue. Reitz serum test revealed a bacterial index of +3 with a morphological index of 90%, and routine blood showed hypochromic microcytic anaemia and leucocytosis. The patient received corticosteroid therapy, anti-leprosy combination therapy, antibiotics, iron tablets and wound care. DISCUSSION: Lucio’s phenomenon consists of skin lesions that range from painful red-black patches to flaky blisters and ulcerations. These lesions usually occur on the lower extremities, and may extend proximally and distally. The lesions improved after administration of corticosteroids and anti-leprosy. Delayed diagnosis leads to significant disability and community transmission of the disease. The later the diagnosis, the more serious the disease becomes and can lead to death due to sepsis. Early diagnosis and appropriate treatment are important. CONCLUSION: Early detection is crucial in order to deliver therapy earlier and prevent disease worsening.